Cloud provider capacity augmentation through automated resource bartering - Goher, S; Bloodsworth, P; Ur Rasool, R; McClatchey, R (Elsevier, 2017)
Growing interest in Cloud Computing places a heavy workload on cloud providers which is becoming increasingly difficult for them to manage with their primary data centre infrastructures. Resource scarcity can make providers vulnerable to significant reputational damage and it often forces customers to select services from the larger, more established companies, sometimes at a higher price. Funding limitations, however, commonly prevent emerging and even established providers from making a continual investment in hardware speculatively assuming a certain level of growth in demand. As an alternative, they may opt to use the current inter-cloud resource sharing systems which mainly rely on monetary payments and thus put pressure on already stretched cash flows. To address such issues, a new multi-agent based Cloud Resource Bartering System (CRBS) is implemented in this work that fosters the management and bartering of pooled resources without requiring costly financial transactions between IAAS cloud providers. Agents in CRBS collaborate to facilitate bartering among providers which not only strengthens their trading relationships but also enables them to handle surges in demand with their primary setup. Unlike existing systems, CRBS assigns resources by considering resource urgency which comparatively improves customers’ satisfaction and the resource utilization rate by more than 50%. The evaluation results verify that our system assists providers to timely acquire the additional resources and to maintain sustainable service delivery. We conclude that the existence of such a system is economically beneficial for cloud providers and enables them to adapt to fluctuating workloads.